Optimizing subpixel rendering using a perceptual metric - Farrell, Joyce; Eldar, Shalomi; Larson, Kevin; Matskewich, Tanya; Wandell, Brian (Journal of The Society for Information Display, 2011)
— ClearType is a subpixel-rendering method designed to improve the perceived quality of text. The method renders text at subpixel resolution and then applies a one-dimensional symmetric mean-preserving filter to reduce color artifacts. This paper describes a computational method and experimental tests to assess user preferences for different filter parameters. The computational method uses a physical display simulation and a perceptual metric that includes a model of human spatial and chromatic sensitivity. The method predicts experimentally measured preferences for filters for a range of characters, fonts, and displays.